Downregulation of tropomyosin 2 promotes the progression of lung adenocarcinoma by regulating neutrophil infiltration through neutrophil elastase - Caixiu Huang; Hao Qiu; Changting Xu; Zilong Tan; Mei Jin; Jing Hu; Zhilong Huang; Yuwei Zhou; Shengyou Ge; Xiaoyuan Hu (Cell Death and Disease)
Abstract Lung adenocarcinoma (LUAD) is a common malignant tumor in the lung that seriously endangers the health of people worldwide. The neutrophil-associated inflammatory microenvironment contributes to the activation of tumor cells. In this study, we report a role of tumor-associated neutrophils (TANs) promote tumor progression of LUAD by crosstalk between neutrophils and tumor cells. Mechanistically, in co-culture with tumor cells, downregulation of TPM2 on tumor cells increases neutrophil elastase (ELANE) levels in neutrophils regulated by p38/ MAPK signaling activation, and ELANE promotes tumor cell progression through the Hippo pathway. Furthermore, downregulation of TPM2 activates ELANE of neutrophils to facilitate ERK1/2 activation, thus enhancing IL1β and IL8 secretion for chemoattraction of more neutrophils to tumor microenvironment. The new studies identify an accomplice role for the interaction between TPM2 and ELANE in promoting LUAD progression and provide potential strategies in the prevention and/or treatment of LUAD and other cancers.